Specific Language for Robot Trajectory Generation - Kaloyan Yankov (JOIV : International Journal on Informatics Visualization, 2017)
In this paper, a programming language for describing trajectories of the Mover 4 educational robot is discussed. The goal is to overcome the limitations of the programming tools provided by the manufacturer. Object-oriented structures of trajectories in the joint space and three-dimensional space are formulated. The model of the trajectory in the joint space is represented by the value of the joint, its velocity and acceleration, and the inertial tensor of the configuration from the respective joint to the end-effector. The inertia tensor is necessary to calculate joint forces and moments. A point from the trajectory in three-dimensional space is defined by the Cartesian coordinates of the end-effector, its orientation with the Euler angles and its velocity. Language offers spatial primitives to describe trajectories formed by segments, circle arcs, and cubic splines. Each primitive has a method of generating intermediate points. The language will allow the study of kinematic and dynamic capabilities in tracking trajectories.